2020
DOI: 10.1001/jamanetworkopen.2020.6039
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Availability of Survey Data About Cannabis Use

Abstract: IMPORTANCEIn response to increasing public support for cannabis legalization, understanding associations of state and federal policy changes related to cannabis legalization with patterns of cannabis use is important. A challenge for public health monitoring and research is significant variation in data availability related to cannabis use behaviors and perceptions across and within states and over time, including the availability of prelegalization vs postlegalization data. OBJECTIVE To review data available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Additionally, the natural turnover between being a cannabis user or not is impossible to assess, and reaching robust conclusions about the effects of the lockdown thus warrants further research. Another limitation concerns the fact that the survey was not validated, although most of the other studies on cannabis use ask a comparable question about consumption ( 47 , 48 ). Similarly, our questionnaire did not produce data about addictive behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the natural turnover between being a cannabis user or not is impossible to assess, and reaching robust conclusions about the effects of the lockdown thus warrants further research. Another limitation concerns the fact that the survey was not validated, although most of the other studies on cannabis use ask a comparable question about consumption ( 47 , 48 ). Similarly, our questionnaire did not produce data about addictive behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term studies are assessing about cannabis use in adolescents, young adults, and adults living in states in which cannabis is legal and illegal (See E-Supplement). 46,47,48 Only J o u r n a l P r e -p r o o f 37.5% of current cannabis users indicated wanting to discuss cannabis with their physician and current cannabis users indicated that 41% of their physicians asked about cannabis either verbally or on an intake form. Perhaps so few cannabis users want to discuss cannabis with their physician because they are deriving beneficial effects that outweigh the impact on their disease and do not want to be told to stop smoking or vaping cannabis, despite the scant research on the long-term effects of inhaling cannabis on the lungs.…”
Section: Discussionmentioning
confidence: 99%
“…This pilot study provides preliminary data examining the association between reasons for product use and co-use behaviors, including direct comparisons of reasons for using vaped nicotine, vaped cannabis, and smoked cannabis. While the measures included in this study provide a more detailed assessment of these issues than what is available in larger-scale surveys (Geissler et al, 2020 ), there are some limitations. First, these findings should be considered exploratory considering the small sample size and convenience sampling method.…”
Section: Discussionmentioning
confidence: 99%